Knowledge on dietary patterns among pregnant women attending antenatal care check-up in Narayani hospital, Nepal - Shah, Sunil; Sharma, Ghanashyam; Shris, Lalkaji; Shah, Sanjay Kumar; Sharma, Mamata; Sapkota, Niraj Khatri (International Journal Of Community Medicine And Public Health, 2017)
Background: Pregnancy is the period from conception to birth during which there is the requirements of diet that provide the required essential nutrients to keep the mother healthy and allow the fetus to grow and develop in favorable conditions. The objective of the study was to identify the knowledge on dietary pattern among pregnant women attending ANC checkup in Narayani sub-regional hospital. Methods: The study was of descriptive, cross sectional type. The random sampling technique was applied. The study design was conducted in Narayani sub-regional hospital in Parsa district, Nepal. Participants included 96 pregnant women using semi structured questionnaire through face to face interview. Data analysis was done both manually and with the help of SPSS. Results: The study showed that there were more women 56(58.3%) from rural areas than that of urban. About seven out of 10 pregnant women were between the ages of 20 to 35 years of age and the study showed that one-fifth of the pregnant women were married before legal age. The mean age of pregnant women was 24. 1 year. There were 6.2% of pregnant women who were illiterate and six out of 10(59.4%) pregnant women had agriculture as their main occupation. The total sampled 96 pregnant women interviewed all knew about nutrition and mostly the source of information was family, neighbors and friends (34.4%). Almost two-fourth (45.8%) of pregnant women still have the wrong perception regarding consumption of green vegetables and coldness (61.4%) is the main reason behind not consumption of green vegetables. The reason for consumption of processed food was because of easy availability and nine in ten pregnant women replied media influenced them to eat processed food. Two-third pregnant women replied right answer for reason of taking iron tabs. In the study found that there is no association between women literacy and knowledge on nutrition. About 6 in 10 (59.3%) sampled women had moderate knowledge on nutrition whereas only one forth-pregnant woman had high knowledge on nutrition. One-sixth pregnant women had low knowledge. Conclusions: The study revealed that, although every pregnant woman had some sorts of knowledge on nutrition, still there is lack of sufficient knowledge on dietary patterns during pregnancy and some wrong perceptions following diet consumption during pregnancy was found. Health education and awareness programs that influences to develop positive attitude can only ultimately brings changes in the behavior.